Software translation specifics and partial automation - Laucius, Rimgaudas (Lietuvos matematikos rinkinys, 2004)
There is analysis of software translation specifics and possibilities of partial automatic translation, presented in this paper. Referencing on statistical text analysis the efficiency of automated translation tools application is estimated.
Keywords: automatic software translation; translation memory